The golden fetters in the mediterranean periphery: How Spain and Italy overcame business cycles between 1870 and 1913? - Alba Roldan (Economics: The Open-Access, Open-Assessment Journal, 2022)
The gold standard was a monetary system based on fixed exchange rates, whereby domestic prices were pegged to the international price level and a high level of control had to be exercised over the money supply. This meant that fiscal discipline also had to be maintained for a country to remain on the gold standard. In times of crisis, countries had to leave the gold standard or use internal devaluation. This article seeks to gain an understanding of the role of the different economic policies in Italy and Spain at the end of the nineteenth century and the beginning of the twentieth century and how they were used in response to reductions in GDP. This article considers fiscal policy, monetary policy, and exchange rate policy estimating a VAR model. Results show how the exchange rate depreciation had positive effects on the Spanish economy during 1870-1913, while it only helped the Italian economy in specific periods to overcome crises. The expansive monetary policy was necessary for both countries to maintain public expenditure, which in turn allowed a smoothing of the GDP fluctuations. None of these policy options would have been available under the gold standard.
Keywords: 330; exchange rate; Italy; monetary policy; monetary system; Spain